Indo-Slang and Identity Performance: The Sociolinguistics of 'Bahasa Anak Jaksel' as a Marker of Neoliberal Class Distinction - Firdhaus, Muhammad; Rajagukguk, Elia Binsar; Gaol, Tiara Boru Lumban (Universitas Negeri Semarang, 2025)
The linguistic phenomenon popularly known as Bahasa Anak Jaksel (South Jakarta slang)—characterized by frequent code-switching between Indonesian and English—has evolved into a significant cultural signifier in contemporary Indonesia. This paper examines the sociolinguistic functions of this hybrid language through the lens of Pierre Bourdieu’s